The GPS integer least-squares statistics. - Teunissen, Peter (2000)
Successful integer least-squares carrier phase ambiguity estimation is the key to fast and high precision GPS kinematic positioning. In order to describe the quality of the positioning results rigorously, one needs to know the probability distributions of both the integer and noninteger parameters in the GPS model. In this contribution these distributions are presented and discussed. The probability mass function of the integer least-squares ambiguities is needed to evaluate the ambiguity success rate and the joint distribution of the GPS baseline and atmospheric delays is needed to evaluate the relevant confidence regions.